ANALYSIS OF RICE CONSUMER PROFILE AND PREFERENCES IN PAGAR MERBAU DISTRICT - Fuad Balatif; Ichpan Zulfansyah; Irshad Ahmad Reshi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to analyze the characteristics and preferences of consumers in consuming rice, both local and national superior rice in Pagar Merbau District. The method used was a survey with an accidental sampling technique on 120 respondents consisting of 105 local rice consumers and 15 national rice consumers. Data were collected through interviews and analyzed using descriptive methods. The results showed that local rice consumers were dominated by the productive age group 26–35 years (36.19%), female (61.90%), had a high school or bachelor's degree, and had incomes in the middle to high range. Meanwhile, national rice consumers tended to be from an older age group, dominated by women (80%), with relatively lower education levels and lower incomes. In general, factors such as age, education, number of dependents, occupation, and income influenced rice consumption preferences. Consumers with higher economic levels and education tended to choose local rice, while consumers with economic limitations preferred national rice.